PENGARUH TEKANAN KERJA, MAHAJEMEN KARIR, DAN KOMPENSASI TERHADAP NILAI PROMOSI KARYAWAN - Rahayu, Sri (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
This study aims to determine whether work pressure, career management, and compensation partially and simultaneously affect employee loyalty to CV. British Education Center Medan. The data analysis technique used is the associative method with the help of the SPSS version 16.0 program. This study uses multiple linear regression analysis. The population in this study were all employees of CV. British Education Center Medan. And a sample of 42 respondents. Primary data collection using a questionnaire. The results showed that work pressure, career management, and compensation partially and simultaneously significantly affected employee loyalty to CV. British Education Center Medan.